Authentic materials in the Business English classroom: Annual Reports - Ruiz-Garrido, Miguel F.; Palmer-Silveira, Juan Carlos Carlos (Kalbotyra, 2015)
International firms are interested in getting the best possible professionals, those who are able to communicate accurately at the workplace. To help them, the use of authentic materials in the classroom can enhance students’ options to succeed in their prospective working environment. From a genre-based perspective, annual reports can be useful for that purpose, as they offer a real corporate image of the companies, helping students to understand better how firms work. This paper shows a practical implementation of three activities that are carried out among three different groups of students at a Spanish public university to promote their communicative skills. To do so we have followed a multimodal approach, so that our students can experience, conceptualize and apply meaning to a genre (annual report), completing some tasks in which they have to communicate in English the information appearing in those texts. The final pedagogical recommendations enhance the benefits of using authentic materials in the English for business communication classroom. The combination of multimodality and genre-based pedagogy lead students to understand the current meaning construction in professional settings.